Entrepreneurial Behaviour of Commercial Floriculture Nursery Owners in Kadiyam of Andhra Pradesh (Indian Journal of Extension Education, 2019)
The study was conducted during the year 2018-19 in Kadiyam of Andhra Pradesh to measure the entrepreneurial behaviour of commercial floriculture nursery owners. Kadiyam mandal was purposefully selected since locale is nationally and internationally known for commercial floriculture nurseries. Three villages with highest number and area under commercial floriculture nurseries namely Kadiyam, Vemagiri and Veeravaram were purposively selected for the study and later 120 nursery owners were selected randomly from the three villages in proportion to the number of nurseries in each village. To quantify the entrepreneurial behaviour of commercial floriculture nursery owners, twelve components like innovativeness, decision making ability, leadership ability, achievement motivation, risk orientation, management orientation, scientific orientation, competition orientation, critical thinking, entrepreneurial self-efficacy, resiliency and locus of control were selected. It was found that more than three-fifth (67.50%) of the commercial floriculture nursery owners possessed medium entrepreneurial behaviour followed by 16.67 per cent of them with high level of entrepreneurial behaviour and only 15.83 per cent of them with low level of entrepreneurial behaviour.